E-Learning Lesson Model for Students Through the Network - วิเชียร อุบลรัตน์; อุคพัชญ์สกุล ปัญชรี; ศรีชาญชัย อัญชณา (Business Administration and Management Journal Review, 2019)
Educational management according to Thailand 4.0 policy emphasizes creating innovative outputs. Having communication and information technology skills applying the explicite knowledge to develop their own works to meet the needs of society Moreover in accordance with the 21st century skill that focuses on encouraging learners to learn on their own. E-learning lessons are computer lesson that use the internet and students studying can study on their own. The content of E-learning lessons will be presented in a multimedia manner. Therefore, E-learning has so many advantages when comparing with the other methods. Especially, data accessibility.The design of instructional management using E-learning lesson through network system is one of the method that help to develop students skills due to repeatly review the lessons. Develop skills by yourself according to your needs at any time.